A health economic outcome evaluation of an internet-based mobile-supported stress management intervention for employees - Ebert, David Daniel; Kählke, Fanny; Buntrock, Claudia; Berking, Matthias; Smit, Filip; Heber, Elena; Baumeister, Harald; Funk, Burkhardt; Riper, Heleen; Lehr, Dirk (Scandinavian journal of work, environment & health, 2018)
Objective This study aimed to estimate and evaluate the cost-effectiveness and cost-benefit of a guided internetand mobile-supported occupational stress-management intervention (iSMI) for employees from the employer's perspective alongside a randomized controlled trial. Methods A sample of 264 employees with elevated symptoms of perceived stress (Perceived Stress Scale, PSS10≥22) was randomly assigned either to the iSMI or a waitlist control (WLC) group with unrestricted access to treatment as usual. The iSMI consisted of seven sessions of problem-solving and emotion-regulation techniques and one booster session. Self-report data on symptoms of perceived stress and economic data were assessed at baseline, and at six months following randomization. A cost-benefit analysis (CBA) and a cost-effectiveness analysis (CEA) with symptom-free status as the main outcome from the employer's perspective was carried out. Statistical uncertainty was estimated using bootstrapping (N=5000). Results The CBA yielded a net-benefit of 181 [95% confidence interval (CI) -6043-1042] per participant within the first six months following randomization. CEA showed that at a willingness-to-pay ceiling of ϵ0, ϵ1000, ϵ2000 for one additional symptom free employee yielded a 67%, 90%, and 98% probability, respectively, of the intervention being cost-effective compared to the WLC. Conclusion The iSMI was cost-effective when compared to WLC and even lead to cost savings within the first six months after randomization. Offering stress-management interventions can present good value for money in occupational healthcare.